2017
DOI: 10.3389/fnins.2017.00307
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Target Analyses of Otx2 Homeoprotein in Postnatal Cortex

Abstract: Juvenile brain has a unique time window, or critical period, in which neuronal circuits are remodeled by experience. Mounting evidence indicates the importance of neuronal circuit rewiring in various neurodevelopmental disorders of human cognition. We previously showed that Otx2 homeoprotein, essential for brain formation, is recaptured during postnatal maturation of parvalbumin-positive interneurons (PV cells) to activate the critical period in mouse visual cortex. Cortical Otx2 is the only interneuron-enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 78 publications
(140 reference statements)
0
38
0
Order By: Relevance
“…In contrast to the prevailing notion that PNN inhibits the plasticity as a physical barrier, a new study using mice lacking a key CS‐synthesizing enzyme, chondroitin sulfate N ‐acetylgalactosaminyltransferase 1 (CSGalNAcT1), showed that a small amount of PNN is essential to open the critical period by promoting accumulation of Otx2 in PV cells (Hou et al., ; Igarashi, Takeuchi, & Sugiyama, ). As CSGalNAcT1 is a target gene of Otx2 (Sakai et al., ), continuous internalization of Otx2 then accelerates further PNN formation, which in turn consolidates PV cell function and closes the critical period. Inhibition of Otx2 internalization in adults, by infusing a peptide that interferes with PNN interaction or by exogenous antibody to trap Otx2, leads to a decrease of PV circuits and reactivation of the critical period (Bernard et al., ; Beurdeley et al., ; Hou et al., ).…”
Section: Otx2 Homeoprotein Is a Messenger Of Experience To Regulate Tmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast to the prevailing notion that PNN inhibits the plasticity as a physical barrier, a new study using mice lacking a key CS‐synthesizing enzyme, chondroitin sulfate N ‐acetylgalactosaminyltransferase 1 (CSGalNAcT1), showed that a small amount of PNN is essential to open the critical period by promoting accumulation of Otx2 in PV cells (Hou et al., ; Igarashi, Takeuchi, & Sugiyama, ). As CSGalNAcT1 is a target gene of Otx2 (Sakai et al., ), continuous internalization of Otx2 then accelerates further PNN formation, which in turn consolidates PV cell function and closes the critical period. Inhibition of Otx2 internalization in adults, by infusing a peptide that interferes with PNN interaction or by exogenous antibody to trap Otx2, leads to a decrease of PV circuits and reactivation of the critical period (Bernard et al., ; Beurdeley et al., ; Hou et al., ).…”
Section: Otx2 Homeoprotein Is a Messenger Of Experience To Regulate Tmentioning
confidence: 99%
“…Otx2 co‐localizes mainly with PV cells across cortical regions such as somatosensory, motor, auditory and cingulate cortexes, and the emergence of Otx2 signals correlates with PV cell development (Sakai et al., ; Spatazza et al., ). Notably, it has been shown that auditory and medial prefrontal cortexes require localization of Otx2 in PV cells for the critical period (Lee et al., ).…”
Section: Otx2 Homeoprotein Is a Messenger Of Experience To Regulate Tmentioning
confidence: 99%
See 3 more Smart Citations